Modeling the endocrine control of vitellogenin production in female rainbow trout - Kaitlin Sundling; Gheorghe Craciun; Irvin Schultz; Sharon Hook; James Nagler; Tim Cavileer; Joseph Verducci; Yushi Liu; Jonghan Kim; William Hayton (Mathematical Biosciences and Engineering)
The rainbow trout endocrine system is sensitive to changes in annual day length, which is likely the principal environmental cue controlling its reproductive cycle. This study focuses on the endocrine regulation of vitellogenin (Vg) protein synthesis, which is the major egg yolk precursor in this fish species.We present a model of Vg production in female rainbowtrout which incorporates a biological pathway beginningwith sex steroid estradiol-17β levels in the plasma andconcluding with Vg secretion by the liver and sequestration in theoocytes. Numerical simulation results based on this model are comparedwith experimental data for estrogen receptor mRNA, Vg mRNA, and Vgin the plasma from female rainbow trout over a normal annual reproductivecycle. We also analyze the response of the model to parameter changes.The model is subsequently tested against experimental data from femaletrout under a compressed photoperiod regime. Comparison of numericaland experimental results suggests the possibility of a time-dependentchange in oocyte Vg uptake rate.This model is part of a larger effort that is developing a mathematical description of the endocrine control of reproduction in female rainbow trout. We anticipate that these mathematical and computational models will play an important role in future regulatory toxicity assessments and in the prediction of ecological risk.